FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN BURNOUT SYNDROME PADA DOSEN FAKULTAS ILMU KESEHATAN UPN VETERAN JAKARTA 2020 - Nelce Tejaruth (2021)
Burnout syndrome is a state of mental and physical exhaustion that can cause a decrease in performance and work performance and can even lead to apathy and cynicism. Lecturers as teaching staffs are in position number two who have the opportunity to experience burnout syndrome. This study aims to determine the factors associated with burnout syndrome in lecturers at the Faculty of Health Sciences, UPN Veteran Jakarta. This study used a quantitative analytical approach with a cross-sectional design. The sampling technique was total sampling with a total sample size of 66 respondents. The variables studied were burnout syndrome, age, gender, years of service, marital status, work-life balance, and workload. The data analyzed were using the chi-square test. The research instrument used was the Maslach Burnout Inventory Educators Survey (MBI-ES), Work-life Balance Scale, NIOSH Generic Job Stress Questionnaire. The results in this study indicate the factors associated with burnout syendrome, among others, the type of gender (p-value = 0.018), work-life balance (p-value = 0.000), and workload (p-value = 0.036). It concluded that UPN Veteran Jakarta is expected to reduce workload, make efforts to improve self-concept, and lecturers are expected to maintain a work-life balance.